Preparation, growth and characterization of nonvacuum Cu-doped ZnO thin films - Asikuzun, E.; Ozturk, O.; Arda, L.; Terzioglu, C. (Elsevier BV, 2018)
Abstract We investigated the effects of increasing Cu dopant concentration on the microstructure and optical properties of Zn1−xCuxO thin films. The transparent Zn1−xCuxO solution concentrations were varied from x = 0.0 to x = 0.05 with an increment of 0.01. All nano films were prepared by dip coating system using the sol-gel method. X-ray diffraction (XRD) measurements, scanning electron microscopy (SEM) observations, energy-dispersive X-ray spectroscopy (EDS) analyses, and atomic force microscopys (AFM) analyses revealed a fine-grained structure resulting from doping of Cu into the ZnO structure. In addition, UV–Vis spectrophotometer was used to determine the optic properties of ZnO based nano thin films. XRD analysis also showed that the undoped ZnO and Cu-doped ZnO films oriented along the (002) as the dominant plane. In the 400–700 nm wavelength range, a decrease in transparency was observed in the Zn1−xCuxO thin films with increasing Cu concentration. Although the optical band gap of the Cu-doped ZnO thin films was lower than that of the undoped ZnO thin film, the Urbach energy of the all of the doped thin films was higher than the undoped ZnO thin film.
Keywords: Sol-Gel; ZnO; Cu-Doping; Thin Film; Optical Properties